2010
DOI: 10.1093/ejo/cjq086
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic treatment need in a 12-year-old population in the Western Sahara

Abstract: The aim of this study was to establish orthodontic treatment need according to the Dental Aesthetic Index (DAI) and Aesthetic Component (AC) and Dental Health Component (DHC) of the Index of Orthodontic Treatment Need (IOTN) and to determine its association with gender among Saharan schoolchildren. The study was carried out in accordance with World Health Organization (WHO) recommendations for oral health surveys at 12 years of age. The sample comprised 248 Sahrawi children (135 girls and 113 boys) living in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 13 publications
7
16
2
1
Order By: Relevance
“…In our study there are no gender differences in the distribution of the orthodontic treatment need. These results are in the line with the results of many studies 17,20,23 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study there are no gender differences in the distribution of the orthodontic treatment need. These results are in the line with the results of many studies 17,20,23 .…”
Section: Discussionsupporting
confidence: 93%
“…Significantly lower DHC IOTN value is found in Iran (18.4%) 22 and the Western Sahara (18.1%) 23 . According to AC IOTN our results 15.3% of the children with the great need for orthodontic treatment is similar to those obtained in the Western Sahara 23 19 . In our study there are no gender differences in the distribution of the orthodontic treatment need.…”
Section: Discussionmentioning
confidence: 82%
“…In France, Souames et al found 21% in a sample of children aged 9 to 12 years (14). In Iran, Hedayati et al obtained similar results (18.4%) in a sample aged between 11 and 14 years, as did Puertes-Fernández et al in a sample of 12-year-old children in the Western Sahara (18.1%) (15,16). …”
Section: Discussionsupporting
confidence: 55%
“…The oral diseases covered in these studies included dental caries experience [ 3 5 , 28 30 , 32 34 , 36 , 41 43 , 48 ], periodontal disease [ 3 , 5 , 8 , 15 , 36 , 42 , 43 , 47 , 48 , 57 ], orthodontic treatment need [ 37 ], enamel fluorosis [ 28 ], oral lesions [ 51 ], and traumatic dental injuries [ 4 , 6 , 14 , 56 ]. Dental caries experience and periodontal status were frequently assessed in accordance with the World Health Organisation recommendations [ 58 ].…”
Section: Resultsmentioning
confidence: 99%